2013
DOI: 10.1177/0193723513491751
|View full text |Cite
|
Sign up to set email alerts
|

An (In)convenient Truce? Paralympic Stakeholders’ Reflections on the Olympic–Paralympic Relationship

Abstract: Formal contractual agreements between the International Olympic Committee (IOC) and International Paralympic Committee (IPC) evince the closer relationship that has been negotiated in recent times between the governing bodies of the Olympic and Paralympic sporting movements. This article explores the IOC–IPC relationship using Paralympic stakeholder perspectives, gathered via semistructured interviews. Utilizing Bourdieusian theory, these insights are analyzed and highlight the complex contestation for multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
(10 reference statements)
0
18
0
2
Order By: Relevance
“…The authors reviewed the recent works of Purdue and Howe (2012a, 2013 who have both independently and collectively focused much of their work on the Paralympic Games and the Olympic-Paralympic relationship applying Bourdieu's sociological lens. Purdue (2013) in his most recent work supports many of the contentions and issues raised in this article albeit from a different theoretical lens resulting in a different conclusion.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The authors reviewed the recent works of Purdue and Howe (2012a, 2013 who have both independently and collectively focused much of their work on the Paralympic Games and the Olympic-Paralympic relationship applying Bourdieu's sociological lens. Purdue (2013) in his most recent work supports many of the contentions and issues raised in this article albeit from a different theoretical lens resulting in a different conclusion.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Another perspective not pursued in the article but certainly worth considering for future research is the potential results of evolving IOC-IPC relations to Paralympic athletes and people with disabilities in general. If the Games and organizations do move closer together, Purdue (2013) has suggested that to market Paralympians as the same as Olympians risks marginalizing certain individuals with impairments, and alienating people with disabilities in general. A human rights and social justice argument could also be applied to this assessment.…”
Section: Ccf-1)mentioning
confidence: 99%
“…Similar trends have occurred internationally particularly in the strengthening of ties between the IPC and the IOC (Brittain, 2009;Howe, 2008;Purdue, 2013). For example, the IOC now selects the host city for the next Olympic and Paralympic Games and represents the IPC in many major negotiations.…”
Section: Advocating For Inclusionmentioning
confidence: 79%
“…Ever since it was created in 1989, the IPC has never ceased to evolve, shifting from a participatory form of sport for people with disabilities -on which it was initially based -to an economy founded on high-performance sport, more recently put forward by the IPC's desire to sell their games and international competitions as shows (Howe, 2008). This development has appeared in a movement of normalization of Paralympic sport, in particular through agreements between the IPC and the International Olympic Committee (IOC) compelling the restructuring of highperformance sport for people with disabilities (Purdue, 2013) The second federations assembly took place four months after the general assembly organized in Beijing by the IPC with a number of decisions making these transformations easy to observe. The General Delegate of the French Paralympic and Sports Committee declared during this assembly that it had been decided at the assembly that "from the opening day of the Paralympic village of the 2020 Games, sports not under the management of an autonomous international federation would be left out of the schedule of events" 8 .…”
Section: Mismatch With International Organizationsmentioning
confidence: 99%